Complement C3a induces axonal hypomyelination in the periventricular white matter through activation of WNT/β‐catenin signal pathway in septic neonatal rats experimentally induced by lipopolysaccharide. (6th November 2019) - Huang, Peixian; Zhou, Qiuping; Lin, Qiongyu; Lin, Lanfen; Wang, Huifang; Chen, Xuan; Jiang, Shuqi; Fu, Hui; Deng, Yiyu
Abstract: Neuroinflammation is thought to play a pivotal role in the pathogenesis of periventricular white matter (PWM) damage (PWMD) induced by neonatal sepsis. Because the complement cascade is implicated in inflammatory response, this study was carried out to determine whether C3a is involved in PWMD, and, if so, whether it would induce axonal hypomyelination. Furthermore, we explored if C3a would act through its C3a receptor (C3aR) and thence inhibit maturation of oligodendrocyte precursor cells (OPCs) via the WNT/β‐catenin signal pathway. Sprague Dawley (SD) rats aged 1 day were intraperitoneally injected with lipopolysaccharide (LPS) (1 mg/kg). C3a was upregulated in activated microglia and astrocytes in the PWM up to 7 days after LPS injection. Concomitantly, enhanced C3aR expression was observed in NG2 + oligodendrocytes (OLs). Myelin proteins including CNPase, PLP, MBP and MAG were significantly reduced in the PWM of 28‐day septic rats. The number of PLP + and MBP + cells was markedly decreased. By electron microscopy, myelin sheath thickness was thinner and the average g‐ratios were higher. This was coupled with an increase in number of NG2 + cells and decreased number of CC1 + cells. Olig1, Olig2 and SOX10 protein expression was significantly reduced in the PWM after LPS injection. Very strikingly, C3aRa administration for the first 7 days could reverse the above‐mentioned pathological alterations in the PWM of septic rats. When incubated with C3a, expression of MBP, CNPase, PLP, MAG, Olig1, Olig2, SOX10 and CC1 in primary cultured OPCs was significantly downregulated as opposed to increased NG2. Moreover, WNT/β‐catenin signaling pathway was found to be implicated in inhibition of OPCs maturation and differentiation induced by C3a in vitro . As a corollary, it is speculated that C3a in the PWM of septic rats is closely associated with the disorder of OPCs differentiation and maturation through WNT/β‐catenin signaling pathway, which would contribute ultimately to axonal hypomyelination.